CATEGORICAL TOOL OF INNOVATIVE LABOR PROVIDING IN MODERN CONDITIONS - Chernoivanova , A. S. (The actual problems of regional economy development, 2017)
The article aims to study theoretical foundations of providing innovative work in modern conditions based on systematizing categorical tools. As a result of the study we found out the innovative work features and singled it out among other related to it categories such as “creative work”, “intellectual work”, “labor management”; summarized theoretical propositions about the nature of innovation work and clarified its definition. Classification of innovative work was grounded. The features of the innovative work were defined. Innovative work was singled out among other related to it types of work.